Factors Affecting Apparel Pattern Grading Accuracy: Existing Software Solutions Comparison and Development of New Solution - Md. Mazharul Islam; Md. Reazuddin Repon; Md. Shohan Parvez; Md. Mahbubul Haque; Mohammad Abdul Jalil (Tekstilec, 2021)
Every so often, grading is not 100% accurate due to the conventional system for calculating the grading increment. The aim of this study was to develop a new calculation system of grading increment provided by different software, e.g. Lectra, Gerber, Optitex, Boke CAD etc., and to develop a new mathematical solution that enhances grading precision. For this experiment, three different spec sheets of different buyers were collected, and then combined and drawn to a solitary sketch for both front and back including all points of measures (POM) for a more easy comparison. The solutions for the presence of diagonal and curve measurements were provided with examples using various tools and techniques of different professional garment CAD software. The benefit of the new approach is not only reduced errors of grading but also guaranteed garment fit without distorting style features. However, the drawbacks of the measurement method are complicated and time-consuming. They revolve around the fact that iterative fitting and adjustments are mandatory to improve the fit before bulk production. The study revealed that this new system slightly increases calculation time, whereas the sample approval time for order execution reduces considerably.